Chromosome polymorphism in the Brazilian dwarf brocket deer, Mazama nana (Mammalia, Cervidae) - Abril, Vanessa Veltrini [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Sociedade Brasileira de Genética, 2008)
The Brazilian dwarf brocket deer (Mazama nana) is the smallest deer species in Brazil and is considered threatened due to the reduction and alteration of its habitat, the Atlantic Rainforest. Moreover, previous work suggested the presence of intraspecific chromosome polymorphisms which may contribute to further population instability because of the reduced fertility arising from the deleterious effects of chromosome rearrangements during meiosis. We used G- and C-banding, and nucleolus organizer regions localization by silver-nitrate staining (Ag-NOR) to investigate the causes of this variation. Mazama nana exhibited eight different karyotypes (2n = 36 through 39 and FN = 58) resulting from centric fusions and from inter and intraindividual variation in the number of B chromosomes (one to six). Most of the animals were heterozygous for a single fusion, suggesting one or several of the following: a) genetic instability in a species that has not reached its optimal karyotypic evolutionary state yet; b) negative selective pressure acting on accumulated rearrangements; and c) probable positive selection pressure for heterozygous individuals which maintains the polymorphism in the population (in contrast with the negative selection for many rearrangements within a single individual).
Keywords: Mazama nana; Brazilian dwarf brocket deer; Cytogenetics; chromosome polymorphism; centric fusions